HASAN EL-BENNÂ'NIN DİN VE SİYASET ANLAYIŞI - AKKOYUNLU, SONGÜL (Fırat Üniveristesi, 2012)
Yirminci yüzyılın en büyük ve en etkili Sünni İslami hareketi olarak kabul edilen İhvân-ı Müslimin teşkilatının kurucusu olan Hasan el-Bennâ, İhvân'ın tarih sahnesine çıktığı 1928 yılından beri dünya gündeminde yerini alan liderlerden biri olmuştur. 20 yıl gibi kısa İhvân başkanlığına rağmen İslam âleminin önde gelen şahsiyetlerinden biri olarak kabul edilmektedir. Kurduğu dinamik, kendini yenileyebilen teşkilatı ile adından söz ettirmiştir.el-Bennâ gerek Mısır'da gerekse ölümünün ardından tüm Müslümanlara fikirleriyle, davasıyla yankı uyandıran bir şahsiyet olmuştur. Kendisi aslında yeni bir görüş veya hareket başlatmamış; selefî görüşleri tekrar eden bir ses olmuştur. Tüm İslam dünyasını kasıp kavuran Batı taklitçiliğine karşı durmuş başta Mısır olmak üzere tüm dünya Müslümanlarını İslam'ın öz kaynaklarına dönmeye davet etmiştir.Anahtar Kelimeler: Hasan el-Bennâ, Selef, İhvân, Mısır.

Hassan al-Banna is the founder of The Society of the Muslim Brothers (The Brotherhood) which is regarded as the biggest and the most effective sunni islamic movement of the twentieth century. The Society of the Muslim Brothers emerged in 1928 and since this date, Hassan al-Banna has been one of the important leaders of world agenda. Even though he has been the leader of The Society of the Muslim Brothers only for twenty years, he is regarded as one of the most important person of the islamic world. Hassan al-Banna has been a famous scholar and schoolteacher with his dynamic and renewable organization, which was founded by himself.In Egypt and after his death in all muslim world, Hassan al-Banna has been a very important person with his opinions and struggle. Indeed he hasn?t start a new idea or movement but he has been a scholar who repeats the opinions of predecessor. Hassan al-Banna has been object to being an imitator of western thought, which damages to all of the muslim world. At the same time he has invited all of the people of muslim world to turn to sources of Islam.Key Words: Hassan al-Banna, predecessor, The Brotherhood, Egypt.
Understanding of religion and politics Hasan el-Bannâ
Keywords: Din